2019
DOI: 10.1186/s12936-019-2705-2
|View full text |Cite
|
Sign up to set email alerts
|

UDP-glycosyltransferase genes and their association and mutations associated with pyrethroid resistance in Anopheles sinensis (Diptera: Culicidae)

Abstract: Background UDP-glycosyltransferase (UGT) is an important biotransformation superfamily of enzymes. They catalyze the transfer of glycosyl residues from activated nucleotide sugars to acceptor hydrophobic molecules, and function in several physiological processes, including detoxification, olfaction, cuticle formation, pigmentation. The diversity, classification, scaffold location, characteristics, phylogenetics, and evolution of the superfamily of genes at whole genome level, and their association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 92 publications
1
52
0
Order By: Relevance
“…Insect UGT genes play diverse roles, including detoxification, digestion, olfaction and pigmentation and they are expressed in many different tissues [15,43]. The over-expressions of UGT genes in insecticide-resistant insects have been reported in Leptinotarsa decemlineata (Say), Plutella xylostella (L.), Diaphorina citri Kuwayama, Tetranychus cinnabarinus (Boisduval), Anopheles sinensis Wiedemann and Aphis gossypii Glover [43][44][45][46][47][48]. It has also been reported that UGTs were induced by insecticide exposures in Spodoptera exigua (Hübner) and Bemisia tabaci (Gennadius) [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Insect UGT genes play diverse roles, including detoxification, digestion, olfaction and pigmentation and they are expressed in many different tissues [15,43]. The over-expressions of UGT genes in insecticide-resistant insects have been reported in Leptinotarsa decemlineata (Say), Plutella xylostella (L.), Diaphorina citri Kuwayama, Tetranychus cinnabarinus (Boisduval), Anopheles sinensis Wiedemann and Aphis gossypii Glover [43][44][45][46][47][48]. It has also been reported that UGTs were induced by insecticide exposures in Spodoptera exigua (Hübner) and Bemisia tabaci (Gennadius) [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on An. sinensis, upregulated expression of UGT308D3 and UGT302A3 were associated with pyrethroid resistance [118]. In Cx.…”
Section: Cuticular Resistancementioning
confidence: 99%
“…Although phase II enzymes are expected to play a similar role as phase I enzymes in the metabolism of plant volatiles, pheromones or diverse odorants [9,16,20,22], no olfactory function was revealed so far in insects. Among phase II ODEs, the study of UGTs received an increasing interest during the last decade, especially with regard to insecticide resistance and plant defense mechanisms [37][38][39][40][41][42][43][44]. This major class of enzymes in the animal kingdom [45,46] catalyzes in insects the conjugation of a glycosyl group brought by a UDP-glycoside to hydrophobic substrates [47,48].…”
Section: Introductionmentioning
confidence: 99%